Multinuclear MRI to disentangle intracellular sodium concentration and extracellular volume fraction in breast cancer - Carlotta Ianniello (Nature Portfolio, 2021)
Abstract The purpose of this work was to develop a novel method to disentangle the intra- and extracellular components of the total sodium concentration (TSC) in breast cancer from a combination of proton ( $$^{1}$$ 1 H) and sodium ( $$^{23}\hbox {Na}$$ 23 Na ) magnetic resonance imaging (MRI) measurements. To do so, TSC is expressed as function of the intracellular sodium concentration ( $$\hbox {C}_{\text {IC}}$$ C IC ), extracellular volume fraction (ECV) and the water fraction (WF) based on a three-compartment model of the tissue. TSC is measured from $$^{23}\hbox {Na}$$ 23 Na MRI, ECV is calculated from baseline and post-contrast $$^{1}$$ 1 H $$\hbox {T}_{{1}}$$ T 1 maps, while WF is measured with a $$^{1}$$ 1 H chemical shift technique. $$\hbox {C}_{\text {IC}}$$ C IC is then extrapolated from the model. Proof-of-concept was demonstrated in three healthy subjects and two patients with triple negative breast cancer. In both patients, TSC was two to threefold higher in the tumor than in normal tissue. This alteration mainly resulted from increased $$\hbox {C}_{\text {IC}}$$ C IC ( $$\sim$$ ∼  30 mM), which was $$\sim$$ ∼  130% greater than in healthy conditions (10–15 mM) while the ECV was within the expected range of physiological values (0.2–0.25). Multinuclear MRI shows promise for disentangling $$\hbox {C}_{\text {IC}}$$ C IC and ECV by taking advantage of complementary $$^{1}$$ 1 H and $$^{23}\hbox {Na}$$ 23 Na measurements.